PENGARUH PERPUTARAN PERSEDIAAN TERHADAP LIKUIDITAS DAN DAMPAKNYA TERHADAP PROFITABILITAS: (Studi Kasus pada PT. Semen Indonesia (Persero) Tbk. Periode 2012-2022) - Irsyad, Ersy Muhamad; Yusnita, Rita Tri; Lestari, Suci Putri (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this study was to determine and analyze the effect of inventory turnover on liquidity as measured by quick ratios and its impact on profitability through the operating profit margin at PT. Semen Indonesia (Persero) Tbk. The research method used is quantitative with a causal method and a case study approach. The data used is secondary data because the data obtained is from the annual and quarterly financial reports of PT. Semen Indonesia (Persero) Tbk., period 2012-2022. The data analysis tool used is path analysis. Based on the research result, it is known that inventory turnover has a positive and insignificant direct effect on liquidity (quick ratios). Inventory turnover has a positive and insignificant direct effect on profitability (operating profit margin). Inventory turnover has no significant effect on profitability through liquidity